2021
DOI: 10.1177/1941738120964817
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Neuromuscular Electrical Stimulation Parameters for Postoperative Quadriceps Strength in Patients After Knee Surgery: A Systematic Review

Abstract: Context: Postoperative quadriceps strength weakness after knee surgery is a persistent issue patients and health care providers encounter. Objective: To investigate the effect of neuromuscular electrical stimulation (NMES) parameters on quadriceps strength after knee surgery. Data Sources: CINAHL, MEDLINE, SPORTDiscus, and PubMed were systematically searched in December 2018. Study Selection: Studies were excluded if they did not assess quadriceps strength or if they failed to report the NMES parameters or qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 79 publications
0
15
0
1
Order By: Relevance
“…It was reported that 50–60% quadriceps muscle strength deficits might occur compared with the preoperative levels ( 23 ). Besides, quadriceps weakness has been found to increase joint loading and contribute to the progress of osteoarthritis ( 42 , 43 ). It is a crucial goal to restore quadriceps strength for postoperative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that 50–60% quadriceps muscle strength deficits might occur compared with the preoperative levels ( 23 ). Besides, quadriceps weakness has been found to increase joint loading and contribute to the progress of osteoarthritis ( 42 , 43 ). It is a crucial goal to restore quadriceps strength for postoperative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…They did not find direct evidence to prove the advantage of NMES on quadriceps muscle strength recovery following TKA by limited (only two) included RCTs ( 44 ). Conley et al conducted a systematic review involving eight RCTs to assess the effect of NMES on quadriceps strength after knee surgery, such as anterior cruciate ligament reconstruction ( n = 5), TKA ( n = 2), and meniscectomy ( n = 1) ( 43 ). They revealed that NMES improved the recovery of quadriceps strength after the knee surgery with grade B evidence ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 10 seconds on/20 seconds off duty cycle for a 15-minute intervention period to begin treatment sessions has been reported as an effective paradigm. 90 Position of application is another factor to consider. Recommendations are to begin NMES application in an extended position adding a prop for the heel to facilitate hyperextension ROM as tolerated.…”
Section: Localized Interventions To Improve Quadriceps Functionmentioning
confidence: 99%